Depletion of the Rho GTPases Cdc42, Rac1 or RhoA reduces PDGF-induced STAT1 and STAT3 signaling - Erik Wåhlén; Johan Lennartsson; Johan Heldin (Biochemistry and Biophysics Reports)
This study investigates the role of Rho GTPases, specifically Cdc42, Rac1, and RhoA, in platelet-derived growth factor receptors (PDGFRα and PDGFRβ) signaling. Signal transducer and activator of transcription (STAT) proteins, essential for cellular processes such as proliferation and immune response, are activated downstream of PDGFRs. Dysregulation of these pathways is linked to various diseases, including cancer. The current study examines the effects of Rho GTPase depletion on PDGFR phosphorylation, STAT protein stability, and downstream signaling. Results indicate that depletion of Cdc42, Rac1, or RhoA impairs PDGFR phosphorylation and reduces STAT1 and STAT3 signaling, without significantly affecting AKT and ERK1/2 pathways. The findings highlight the critical regulatory roles of Rho GTPases in PDGFR-mediated STAT signaling.